Game analysis on regenerative synergy mechanism of the supply chain of integrate infrastructure engineering - Zhao, Na; Ma, Bingqi; Li, Xiaolian (Mathematical biosciences and engineering : MBE, 2023)
How to ensure the smooth implementation of convergent infrastructure engineering as the risk of sudden public events persists, allowing the engineering supply chain companies to break through the blockages to regenerate collaboratively and form a regenerated collaborative union. By establishing a mathematical game model, this paper explores the synergistic mechanism of supply chain regeneration for convergent infrastructure engineering, which takes into account cooperation and competition, investigates the impact of supply chain nodes' regeneration capacity and economic performance, as well as the dynamic changes in the importance weights of supply chain nodes, when adopting the collaborative decision of supply chain regeneration, the benefits of the supply chain system, are more than those when suppliers and manufacturers "act of one's own free will" by making decentralized decisions to undertake supply chain regeneration separately. All the investment costs of supply chain regeneration are higher than those in non-cooperative games. Based on the comparison of equilibrium solutions, it was found that exploring the collaborative mechanism of its convergence infrastructure engineering supply chain regeneration provides useful arguments for the emergency re-engineering of the engineering supply chain with a tube mathematical basis. Through constructing a dynamic game model for the exploration of the supply chain regeneration synergy mechanism, this paper provides methods and support for the emergency synergy among subjects of infrastructure construction projects, especially in improving the mobilization effectiveness of the entire infrastructure construction supply chain in critical emergencies and enhancing the emergency re-engineering capability of the supply chain.